Factors forming the BRCA1-A complex orchestrate BRCA1 recruitment to the sites of DNA damage. (1st July 2016) - Her, Joonyoung; Soo Lee, Nam; Kim, Yonghwan; Kim, Hongtae
Abstract : Sustaining genomic integrity is essential for preventing onset of cancers. Therefore, human cells evolve to have refined biological pathways to defend genetic materials from various genomic insults. DNA damage response and DNA repair pathways essential for genome maintenance are accomplished by cooperative executions of multiple factors including breast cancer type 1 susceptibility protein (BRCA1). BRCA1 is initially identified as an altered gene in the hereditary breast cancer patients. Since then, tremendous efforts to understand the functions of BRAC1 reveal that BRCA1 is found in distinct complexes, including BRCA1-A, BRCA1-B, BRCA1-C, and the BRCA1/PALB2/BRCA2 complex, and plays diverse roles in a context-dependent manner. Among the complexes, BRCA1-A is critical for BRCA1 recruitment to the sites of DNA damage. Factors comprising the BRCA1-A include RAP80, CCDC98/Abraxas, BRCC36, BRCC45, BARD1, BRCA1, and MERIT40, a RAP80-associated factor. In this review, we summarize recent findings of the factors that form the BRCA1-A complex.